Multihop relaying for broadband wireless mesh networks from theory to practice. - Oyman, Ozgur (IEEE Communications magazine)
We summarize capacity results to show merits of multihop relaying in broadband cellular mesh networks. Under the guidance of these results, we provide design perspectives on relay deployment, spectrum allocation, and end-to-end optimization of certain QoS measures such as throughput, coverage, reliability, and robustness. We conclude with an overview of recent standardization activities and remarks on remaining open problems and design challenges.